EARLIER FORMAL ETHICS EDUCATION, THE IMPORTANCE OF MEICAL ETHICS AND EXPECTATION OF ETHICS DOCTOR IN FIRST GRADE MEDICAL STUDENTS OF MEDICAL FACULTY UNIVERSITAS TANJUNGPURA PONTIANAK - Ita Armyanti; Mardhia Mardhia; Arif Wicaksono (Faculty of Medicine, Universitas Andalas, 2014)
AbstractHealth care decisions are based not only on clinical and technical grounds, but also onethical grounds. Although we carefully weigh the clinical and technical aspects, ethical issuesinvolved may be overlooked. A legal framework or code of conduct governing doctor's decisionsand behaviour may help overcome this problem but they often provide rigid guidelines for alimited number of situations. Earlier education in ethics might have some advantages to build agood medical character. The perception of the importance of medical ethics could also had aneffect to the expectation of a good medical doctor should be. This research was a cross sectionalstudy in first grade medical students of medical faculty Universitas Tanjungpura Pontianak,conducted in the last week of April, 2014. All of first grade medical students participated in thisstudy. This subjects given questionaire contained several questions : did they ever get a lessonof ethics in their Senior high schcol, how important the medical ethics and after studied medicalethics, what were their expectation ?. 86 subjects participated, 3'1 (36,05%) subjects are maleand 55(63,95%) subjects are female. The Age range from 16-20 years old, median 1B years oldand mode 1B years old. The subject came from 39 senior high school, was spread from papua,java dan kalimantan. Only 10(25,64%) senior high school had been given ethics in theircurriculum and this'1C school all located in Kalinrantan. One subject (1,16%)stated that ethicsjust a common lesson while 35 (40,7A %)subjects stated ihat ethics was inrportani and most ofthe subjects, 50(58,14%) subjects stated that ethics was very important lesson. The expectationafter studying medical ethics are : 39(45,35 o/o) subjects: respect and emphatize the other people,17 (19.77%) subjeets : be a betier person, 14(16,28o/c) subjeets: hospitable docior, 11 (12,79o/o)sub;ects :Apply the basic principle of bioethics and 5 (5,81%) sublects :treat the other like we'dlike to be treated. Twenty five point sixtyfour percent of the prirhary school of first year medicalstudent gave ethics lesson. Most of Subject stated that medical ethics is a very important lesson.The expectation after studying medical ethics varies: respect and emphatize the other people, bea better person, hospitable doctor, Apply the basic principle of bioethics and treat the other likewe'd like to be treated.Affiliasi Penulis: l.Departement of Pharmacology, Medical Faculty Universitas Tanjungpura,2.Depa(ement oftr4icrobiology Medical Faculty Universitas Tanjungpura, 3. Departement of Anatomy Medical Faculty UniversitasTanjungpura, Korespcndensi :Arif Wicaksono, email :drarii,vicaksono@gmail.com.*@TEilSupplen-ren Majalah Kedokteran Andalas' Vol' 37' No Supl'1' Maret 2014ETIKoLEGAL,SEcoNDoPINIONDENGANSENGKETAMEDISNoorman HerryadiKorespondensi : Noorman Herryadi' email : noormanherryadi@yahoo'com'oortr